2016
DOI: 10.1371/journal.pone.0152383
|View full text |Cite
|
Sign up to set email alerts
|

Deltamethrin-Mediated Toxicity and Cytomorphological Changes in the Midgut and Nervous System of the Mayfly Callibaetis radiatus

Abstract: Immature instars of mayflies are important constituents of the food web in aquatic ecosystems (especially in Neotropical regions) and they are among the most susceptible arthropods to pyrethroid insecticides. These insecticides have been recognized as important stressors of freshwater ecosystems, but their cellular effects in aquatic insects have been neglected. Here, we assessed the susceptibility to deltamethrin (a typical type II pyrethroid) as well as the deltamethrin-mediated cytomorphological changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 61 publications
(52 reference statements)
2
15
2
1
Order By: Relevance
“…However, based on our results for deltamethrin toxicity, such conclusions should be analyzed with caution. Whereas the susceptibility of B. tarsalis to deltamethrin (LC50 ¼ 4.0 ng a.i./L) was similar to that of other backswimmer species (e.g., Anisops sardeu) in the subfamily Anisopinae [30], the deltamethrin LC50 for M. bentoi was several fold higher than that for B. tarsalis and A. sardeu, which reinforces the idea that differences in the toxicodynamics of insecticide poisoning, or in physiological and biochemical peculiarities associated with each aquatic insect species, regulate the susceptibilities of these organisms to insecticide exposure [1,4,14,15,26].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, based on our results for deltamethrin toxicity, such conclusions should be analyzed with caution. Whereas the susceptibility of B. tarsalis to deltamethrin (LC50 ¼ 4.0 ng a.i./L) was similar to that of other backswimmer species (e.g., Anisops sardeu) in the subfamily Anisopinae [30], the deltamethrin LC50 for M. bentoi was several fold higher than that for B. tarsalis and A. sardeu, which reinforces the idea that differences in the toxicodynamics of insecticide poisoning, or in physiological and biochemical peculiarities associated with each aquatic insect species, regulate the susceptibilities of these organisms to insecticide exposure [1,4,14,15,26].…”
Section: Discussionsupporting
confidence: 75%
“…The susceptibility of aquatic insects to insecticides is related to physiological and behavioral constraints associated with aquatic ecosystems [1,15,20,26,27]. In the present study we demonstrated that 2 phylogenetically related backswimmer species (B. tarsalis and M. bentoi) had different susceptibilities to deltamethrin, which also had effects on individual swimming activities.…”
Section: Discussionmentioning
confidence: 52%
“…The strongly basophilic nature of the microvilli of region III cells of the midgut (a characteristic not reported by Richardi et al () in C sancticaroli ) could be associated to the high presence of acid‐rich (DNA and RNA) organelles, such as the rough endoplasmic reticulum, the Golgi apparatus and free ribosomes, which indicate a secretory function of mitochondria in order to provide energy for active transport and the intake of substances (Jarial & Engstrom, ). Several studies in insects have shown that the midgut is a target organ for contamination, due to the absorption of xenobiotic substances acquired orally (El‐Saad, Kheirallah, & El‐Samad, ; Gutiérrez, Santos, Serrão, & Oliveira, ; Sumida et al, ). Nevertheless, there are few studies that have applied histopathological markers in the midgut of Chironomidae larvae (Lavarías et al, ; Rey, Long, Pautou, & Meyran, ; Rey, Pautou, & Meyran, ; Richardi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pyrethroid insecticides, the resistance management is complicated because resistance occurs in a variety of forms, including reduced insecticide penetration, metabolic resistance (through detoxification enzymes), behavioral resistance and target-site alterations 1 , 2 . Although the pyrethroid insecticides exert their toxicity primarily by disrupting the function of the voltage-gated sodium channels in excitable cells 3 8 , these compounds also have secondary action targets (e.g., ionic imbalance and osmoregulatory dysfunction) that contribute to their activity 9 11 .…”
Section: Introductionmentioning
confidence: 99%